Odpowiedzi

2010-04-07T20:46:14+02:00
1)
-2(a+1) -y = 7y +5ay
-2a -2 -y = 7y +5ay /+y
-2a- 2=8y+5ay /+2
-2a=8y + 5ay +2 /:(-2)
a=-4y-2,5ay-1
------------------------------
2)
3ab -7 +4b -2(3-a) - 2b -3 ?
-------------------------------
3)
5(a-2) - c =3c + 6ac
5a-10-c=3c+6ac /+c
5a - 10=4c+6ac /+10
5a=4c+6ac+10 /:5
a=4/5c + 6/5ac+2
-------------------------------
4)
5ax - 7 + 4x = -3(3-a) - 2x + 1
5ax-7+4x=-8+3a-2x /+8
5ax+1+4x=3a-2x /+2x
5ax+1+6x=3a / :3
5/3ax+1/3+2x=a
------------------------------
Mam nadzieję że pomogłam ;)